Optimizing Fuzzy Grid Partition Performance for Rule Generation - Essowèmlou Jürgen (International Journal of Enterprise Modelling, 2020)
This research focuses on optimizing the performance of fuzzy grid partitioning for rule generation. Fuzzy grid partitioning is a widely used technique for extracting rules from data, but it faces challenges related to computational complexity, rule redundancy, rule quality, grid size determination, and interpretability. To address these challenges, we propose a mathematical formulation and explore techniques to enhance the efficiency and effectiveness of the rule generation process.The research aims to minimize computational complexity by introducing parallel processing and dynamic grid density adjustment methods. By reducing the time required for grid generation and rule generation, we enable the application of fuzzy grid partitioning to larger datasets. To improve rule quality, we investigate techniques to reduce rule redundancy and enhance rule quality metrics such as accuracy, precision, or coverage. This ensures the generation of accurate and meaningful rules that capture the underlying patterns in the data. Grid size determination is a critical aspect of fuzzy grid partitioning. We explore techniques to determine the optimal grid size, striking a balance between granularity and computational efficiency. This enables the capturing of important patterns in the data while avoiding excessive computational complexity. Interpretability is vital for the acceptance and utilization of generated rules. We propose methods to minimize interpretability measures such as rule length or linguistic complexity, resulting in concise and understandable rule sets. Real-world datasets are used to evaluate the proposed techniques and algorithms, demonstrating their applicability and generalizability. The research outcomes have practical implications in domains such as data mining, machine learning, and expert systems. In conclusion, this research contributes to the optimization of fuzzy grid partitioning for rule generation. The proposed techniques enhance the efficiency, effectiveness, scalability, and interpretability of rule-based systems. The findings empower researchers and practitioners to generate high-quality and interpretable rule sets from large and complex datasets.